Strategi Komunikasi Humas Polres Karawang dalam Upaya Penanganan Berita Hoax di Media Sosial - Rahmania, Adinda; Nayiroh, Luluatu; Susanto, Tri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to determine the communication strategy used by the public relations police of the city of Karawang (Humas Polres Karawang) in dealing with hoaxes on social media. Hoax news is still a national problem that occurs among the public, such as the case of widespread social media coverage that occurred in Karawang in October 2022 related to security disturbances. The research method used is a qualitative method with a case study approach. The research data were obtained through observation, interviews with the Kasubsi Pensat Polres Karawang and documentation. The results of the research show that the planning and management carried out by public relations of the subregional police Karawang in dealing with fake news is identifying news by conducting research to find facts and opinions that are developing in the community about circulating cases. Then, the data found is confirmed through messages in the form of video content and captions containing news value. After that, it was communicated to the public through the official social media police of the city of Karawang (Polres Karawang). Another effort is to conduct socialization to provide education to the public through social media by creating content that is packaged in a fun way. The subregional police Karawang through the Bhabinkamtibmas line of the sector police (Polsek) also carry out humanist-based visits and patrols using local languages ​​so that they are easily accepted by the community by inserting messages to the public not to be consumed by negative issues. Keywords: Hoax; Communication Strategy; Public Relations; POLRI.